The Effect of Government Quality on Foreign Investment: Empirical Study on ASEAN Developing Countries - Drajat, Estu Unggul (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
Introduction: Many ASEAN nations face governance challenges and high corruption, especially Cambodia, Myanmar, and Laos, categorizing most as developing countries. Foreign capital inflows are essential for economic growth, requiring governments to create favorable investment climates. While good governance can attract foreign direct investment (FDI), this relationship is inconsistent. This study aims to determine how government quality affects foreign investment (Foreign Direct Investment). Research Methods: In this study, secondary data is used using quantitative methods. Developing countries in ASEAN are used as samples in this study. Results: This study provides results that political stability and legal regulations have a significant positive impact on Foreign Direct Investment, while corruption control, government effectiveness, and voting rights and accountability hurt FDI. Conclusion: The study has three fundamental implications: it enhances understanding of government quality's impact on foreign investment in developing ASEAN countries, serves as a reference for further research, and offers insights for policymakers to improve regulations and investment climates.